Transient heat transfer characteristics of array-jet impingement on high-temperature flat plate at low jet-to-plate distances. (December 2018) - Zhu, Keqian; Yu, Pingping; Yuan, Ningyi; Ding, Jianning
Highlights: Transient heat transfer characteristics of array-jet impingement is studied. A turning point exists at H / D  = 0.4, and the quenching time is divided into two region. The quenching time decreased as the S / D ratio increased. The flow velocity near the stagnation point region increased as H / D decreased. Abstract: Numerical studies on the transient heat transfer characteristics of air-array-jet impingement, for small jet-to-plate distances and a large temperature difference between the nozzle and plate, are presented. The total mass flow rate of the jets ( m ̇ ) is constant at 30.34 kg/h. The nondimensional jet-to-plate distance ( H / D ) for a nozzle diameter ( D ) of 5 mm is varied from 0.2 to 1. The nondimensional hole-to-hole spacing is S / D  = 5, 7, and 10, respectively. The variations in the transient heat transfer characteristics and flow velocity at different values of H / D and S / D, as a function of the cooling time, are discussed. It is found that there exists a turning point H / D  = 0.4 in the effect of the transient heat transfer. As H / D is decreased, the quenching time shrinks quickly. The velocity field is proposed as an explanation for the observed transient heat transfer. In addition, an appropriate proposal is presented for designing equipments of tempering ultra-thin glass.